(untitled) (The Journal of Plant Protection Sciences, 2021)
The mulberry whitefly, Dialeupora values of these three insecticides were worked decempuncta Quaintance & Baker (Homoptera: out as 0.0131%, 0.0635% and 0.0047% Aleyrodidae) has been found on mulberry from respectively by Patnaik et al. (4). Hence it was 1994 causing a severe damage to the foliage, felt necessary to study the field efficacy of these which is the sole food plant for the silkworm, three insecticides which in turn will cause Bombyx mori L. They suck leaf sap causing minimum adverse effect on environment and chlorosis, dryness of leaves, leaf curl and sooty also to find out its optimum period in becoming mould disease and results a culminating loss in free from toxicity after spraying these leaf yield to the tune of 10-24% especially during insecticides on mulberry for silkworm’s major silkworm cocoon crop seasons. The consumption.